Expanding the Theory of Planned Behavior with Entrepreneurial Intent as a Key Driver in Medan - Simanihuruk , Peran; Syaifuddin; Toni , Nagian (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
Entrepreneurship is vital for economic growth, yet Indonesia’s entrepreneurial rate remains low. This study extends the Theory of Planned Behavior (TPB) by integrating self-confidence and entrepreneurial intent as mediating variables. Using a case study in Medan, data from 400 entrepreneurs were collected via questionnaires and analyzed using Smart PLS 4.0. The findings confirm that entrepreneurial attitude, subjective norms, and perceived behavioral control positively influence entrepreneurial intent and behavior. Self-confidence significantly affects entrepreneurial intent but does not directly impact entrepreneurial behavior. However, entrepreneurial intent mediates the relationship between self-confidence and entrepreneurial behavior, emphasizing the critical role of intent in translating psychological and social factors into entrepreneurial action. These results highlight the need for a supportive entrepreneurial ecosystem encompassing education, industry collaboration, and policy interventions. Practical implications suggest entrepreneurship training programs emphasizing business simulations, mentorship, and confidence-building strategies. Additionally, access to financial resources, social support, and favorable regulatory frameworks is essential for fostering entrepreneurial success. By refining the TPB framework with self-confidence and entrepreneurial intent, this study provides both theoretical insights and practical strategies for strengthening entrepreneurship in Medan and beyond. Future research should explore longitudinal data and comparative regional studies to deepen the understanding of entrepreneurial decision-making.